Chapter Geomorphological approaches to study Posidonia banquettes and their effects on the coastal front of Schinias - Marathon National Park - Kourliaftis, Ioannis (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
UAV technology is used to map the beach morphological characteristics aiming to the impact of the presence of Posidonia οceanica beach-cast seagrass litter in the area of Schinias national Park, Marathon, Greece. Additionally, shoreline change investigation with remote sensing techniques covering a period of 76 years was realized. The role of banquettes seems to be of particularly significant as it is affecting the configuration of coastal front. More extensive monitoring, is required to better comprehend the role of Posidonia banquettes for management planning and decision-making processes.